Microscopic evidence of the metalation of a free-base porphyrin monolayer with iron - Buchner, Florian; Schwald, Veronika; Comanici, Karmen; Steinrück, Hans-Peter; Marbach, Hubertus (ChemPhysChem, 2007)
Microscopic evidence of the in situ complexation of Fe-porphyrins is presented. The figure shows the sub-molecular resolved scanning tunneling microscopy images which document the metalation of 2H-TPP (central cavity; TPP: tetraphenylporphyrin) with evaporated iron (protrusions are identified as Fe-TPP). This promising technique enables future surface science investigations of clean iron porphyrin films under ultrahigh vacuum conditions. © 2007 Wiley-VCH Verlag GmbH & Co. KGaA.